Central nervous system manifestations of neurofibromatosis type 2: A case report - Zineb Izi, MD; Kaoutar Imrani, MD; Najwa Amsiguine, MD; Tlaite Oubaddi, MD; Nabil Moatassim Billah, PhD; Ittimade Nassar, PhD (Radiology Case Reports, 2023)
Neurofibromatosis type 2 (phacomatosis) is a rare inherited autosomal dominant condition defined by the development of numerous central neuronal tumors. In addition to classic intracranial schwannomas, intracranial and spinal meningiomas, and intramedullary ependymomas, it can be associated with a few cutaneous abnormalities. In this report, we discuss the case of a 21-year-old female who was examined for persistent headache with cutaneous masses and bilateral hearing loss. Magnetic resonance imaging of the cranium and the whole spine detected multiple meningiomas, intracranial, and intramedullary tumors.